Molecular detection of fungi of public health importance in wild animals from Southern Brazil - Losnak, Debora O. [UNESP]; Rocha, Francielle R.; Almeida, Barbara S.; Batista, Keila Z. S.; Althoff, Sérgio L.; Haupt, Josiane; Ruiz, Luciana S.; Anversa, Laís; Lucheis, Simone B.; Paiz, Laís M.; Donalisio, Maria Rita; Richini Pereira, Virginia B. (Wiley, 2018)
Some animals have an important relationship with fungal infections, and searching for pathogens in animal samples may be an opportunity for eco-epidemiological research. Since studies involving wildlife are generally restricted, using samples from road kills is an alternative. The aim of this study was to verify whether pathogenic fungi of public health importance occur in wildlife road kills from Santa Catarina State, Brazil. Organ samples (n = 1063) from 297 animals were analysed according to Polymerase Chain Reaction (PCR) using universal primers to detect fungi in general and, subsequently, using primers specific to Paracoccidioides brasiliensis, Histoplasma capsulatum and Cryptococcus spp. There were 102 samples positive for fungal species. Eight samples were positive for P. brasiliensis, three samples were positive for Cryptococcus spp. and one sample had coinfection by these two fungi. No sample was positive for Histoplasma spp. according to the molecular detection. Genetic sequencing allowed the identification of Fungal sp. in 89 samples, Cryptococcus neoformans in two samples and Aspergillus penicillioides in three samples. This study shows the importance of wild animals in the epidemiology of fungal infections and assists in the mapping of pathogen occurrence in a region that was not previously evaluated.
Keywords: Aspergillus penicillioides; Cryptococcus spp.; Histoplasma capsulatum; Paracoccidioides brasiliensis; pathogenic fungi; PCR